Efektivitas Model Contextual Teaching and Learning dalam Meningkatkan Keterampilan Berbicara di SD Negeri 04 Langgam - Ernawati, Ernawati; Marni, Santi; Animah, Siti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Speaking skills are an important aspect of language learning that students need to master in order to be able to communicate effectively. However, many students experience difficulties in speaking fluently, confidently and structurally due to learning methods that are less contextualised. This study aims to analyse the effectiveness of the Contextual Teaching and Learning (CTL) model in improving students’ speaking skills at SDN 04 Langgam. This research uses the Classroom Action Research (PTK) method which consists of several cycles with the stages of planning, implementation, observation, and reflection. The research subjects were 30 grade V students. Data were collected through observation, speaking skill tests, interviews, and documentation, then analysed descriptively. The results showed that the application of the CTL model improved students’ fluency, confidence, and sentence structure in speaking. Real context-based activities, such as discussion, role play, and simulation, contributed to the improvement of speaking skills. Teachers also found it useful in creating a more interactive learning environment. In conclusion, the CTL model is effective in improving students’ speaking skills by involving hands-on experience in learning. Therefore, this approach is recommended to be applied in language teaching in primary schools.